Pat hophysiology of preeclampsia: update - Gómez Carbajal, Luis Martín (2015)
Preeclampsia is one of the most frequent and serious disorders of pregnancy. It is a significantcontributor of maternal and perinatal mortality worldwide. An important amount of researchhas been devoted in the research of preeclampsia in the recent years; nonetheless, itspathophysiology is yet to be completely understood. In this review, we will discuss newproposed theories on the pathophysiology of preeclampsia. Genetic and angiogenic aspectsof preeclampsia will be reviewed elsewhere in this issue.Keywords: placental ischemia, endothelial dysfunction, nitric oxide, oxidative stress,endoplasmic reticulum stress, Chlamydia pneumoniae, fetuin-A